A novel KCND3 variant in the N-terminus impairs the ionic current of Kv4.3 and is associated with SCA19/22 - Reis, Marlen Colleen; Mandler, Laura; Kang, Jun-Suk; Oliver, Dominik; Halaszovich, Christian; Nolte, Dagmar; Justus Liebig University Giessen (My University, 2024)
Spinocerebellar ataxias (SCAs) are a genetically heterogeneous group of autosomal dominant movement disorders. Among the SCAs associated with impaired ion channel function, SCA19/22 is caused by pathogenic variants in KCND3, which encodes the voltage-gated potassium channel Kv4.3. SCA19/22 is clinically characterized by ataxia, dysarthria and oculomotor dysfunction in combination with other signs and symptoms, including mild cognitive impairment, peripheral neuropathy and pyramidal signs. The known KCND3 pathogenic variants are localized either in the transmembrane segments, the connecting loops, or the C-terminal region of Kv4.3. We have identified a novel pathogenic variant, c.455A>G (p.D152G), localized in the N-terminus of Kv4.3. It is located in the immediate neighbourhood of the T1 domain, which is responsible for multimerization with the β-subunit KChIP2b and thus for the formation of functional heterooctamers. Electrophysiological studies showed that p.D152G does not affect channel gating, but reduces the ionic current in Kv4.3, even though the variant is not located in the transmembrane domains. Impaired channel trafficking to the plasma membrane may contribute to this effect. In a patient with a clinical picture corresponding to SCA19/22, p.D152G is the first pathogenic variant in the N-terminus of Kv4.3 to be described to date with an effect on ion channel activity.
Keywords: ddc:610